Daya Saing Minyak Kelapa Sawit Indonesia di Pasar Eropa Barat, Amerika Serikat, dan Jepang - Dradjat, Bambang; Hadi, Prajogo U. (Jurnal Agro Ekonomi, 1996)
Until the early 1990's, the competition of palm oil in international markets has been dominated by Malaysian palm oil. It is believed that Indonesian palm oil is less competitive that of Malaysian's palm in the markets. The objectives of the present study are to analyse the competitiveness of Indonesian palm oil in the international markets, and to formulate strategies for market development. A Market-share approach is used to estimate the competitiveness of palm oil from Indonesia, Malaysia, and the Rest of the World (ROW) in West European, the United States, and Japanese markets. The results show that Indonesian palm oil is relatively competitive in comparison to that of Malaysian and ROW in most of the markets. Strategies to enhance market development for Indonesian palm oil are necessary. In the West European market, strategies to increase or to maintain market shares of Indonesian palm oil is of importance. In the United Kingdom, Netherlands, and German markets, in particular, the strategies have to take market situation of soybean oil into account. In the US and Japanese markets, strategies to penetrate or expand market is essential. These market development strategies deserve market and marketing supports.